Neratinib after trastuzumab-based adjuvant therapy in HER2-positive breast cancer (ExteNET): 5-year analysis of a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 12 (December 2017) - Martin, Miguel; Holmes, Frankie A; Ejlertsen, Bent; Delaloge, Suzette; Moy, Beverly; Iwata, Hiroji; von Minckwitz, Gunter; Chia, Stephen K L; Mansi, Janine; Barrios, Carlos H; Gnant, Michael; Tomašević, Zorica; et al.
Summary: Background: ExteNET showed that 1 year of neratinib, an irreversible pan-HER tyrosine kinase inhibitor, significantly improves 2-year invasive disease-free survival after trastuzumab-based adjuvant therapy in women with HER2-positive breast cancer. We report updated efficacy outcomes from a protocol-defined 5-year follow-up sensitivity analysis and long-term toxicity findings. Methods: In this ongoing randomised, double-blind, placebo-controlled, phase 3 trial, eligible women aged 18 years or older (≥20 years in Japan) with stage 1–3c (modified to stage 2–3c in February, 2010) operable breast cancer, who had completed neoadjuvant and adjuvant chemotherapy plus trastuzumab with no evidence of disease recurrence or metastatic disease at study entry. Patients who were eligible patients were randomly assigned (1:1) via permuted blocks stratified according to hormone receptor status (hormone receptor-positive vs hormone receptor-negative), nodal status (0 vs 1–3 vs or ≥4 positive nodes), and trastuzumab adjuvant regimen (given sequentially vs concurrently with chemotherapy), then implemented centrally via an interactive voice and web-response system, to receive 1 year of oral neratinib 240 mg/day or matching placebo. Treatment was given continuously for 1 year, unless disease recurrence or new breast cancer, intolerable adverse events, or consent withdrawal occurred. Patients, investigators, and trial funder were masked to treatment allocation. The predefined endpoint of the 5-year analysis was invasive disease-free survival, analysed by intention to treat. ExteNET is registered withClinicalTrials.gov, numberNCT00878709, and is closed to new participants. Findings: Between July 9, 2009, and Oct 24, 2011, 2840 eligible women with early HER2-positive breast cancer were recruited from community-based and academic institutions in 40 countries and randomly assigned to receive neratinib (n=1420) or placebo (n=1420). After a median follow-up of 5·2 years (IQR 2·1–5·3), patients in the neratinib group had significantly fewer invasive disease-free survival events than those in the placebo group (116 vs 163 events; stratified hazard ratio 0·73, 95% CI 0·57–0·92, p=0·0083). The 5-year invasive disease-free survival was 90·2% (95% CI 88·3–91·8) in the neratinib group and 87·7% (85·7–89·4) in the placebo group. Without diarrhoea prophylaxis, the most common grade 3–4 adverse events in the neratinib group, compared with the placebo group, were diarrhoea (561 [40%] grade 3 and one [<1%] grade 4 with neratinib vs 23 [2%] grade 3 with placebo), vomiting (grade 3: 47 [3%] vs five [<1%]), and nausea (grade 3: 26 [2%] vs two [<1%]). Treatment-emergent serious adverse events occurred in 103 (7%) women in the neratinib group and 85 (6%) women in the placebo group. No evidence of increased risk of long-term toxicity or long-term adverse consequences of neratinib-associated diarrhoea were identified with neratinib compared with placebo. Interpretation: At the 5-year follow-up, 1 year of extended adjuvant therapy with neratinib, administered after chemotherapy and trastuzumab, significantly reduced the proportion of clinically relevant breast cancer relapses—ie, those that might lead to death, such as distant and locoregional relapses outside the preserved breast—without increasing the risk of long-term toxicity. An analysis of overall survival is planned after 248 events. Funding: Wyeth, Pfizer, and Puma Biotechnology.